Flypaper Effect pada Pendapatan Asli Daerah (PAD) dan Dana Alokasi Umum (DAU) Terhadap Belanja Daerah di Kota Mataram - Sofhia, Sofhia; Priyambodo, Victoria K. (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The regional autonomy system is an effort given to regional governments in the form of authority to manage and administer local affairs in accordance with the needs and characteristics of each region. Sources of regional income can come from, among others, the General Allocation Fund and Original Regional Income. The Flypaper Effect phenomenon can occur when local governments prioritize using transfer funds rather than PAD to meet spending needs. This research is a quantitative descriptive study to look at the Flypaper Effect phenomenon in Mataram City. The results show that Mataram City during the 2018 - 2022 period using Descriptive Statistical Analysis - Crosstab did not experience the Flypaper Effect phenomenon because Regional Original Income (PAD) on Regional Expenditures was greater than the General Allocation Fund (DAU) on Regional Expenditures. The results of this research indicate that the DAU allocation in Mataram City is in accordance with the aim of DAU allocation by the central government, namely encouraging a region to increase its own regional income by optimizing the potential and wealth that exists in that region